Cyberbullying in Portugal. A scoping study and the perceptions of Portuguese teachers - Coutinho, Luis Filipe; Tomás Almeida, Ana Maria; Lescastre, José Alberto (Journal of Learning Styles, 2023)
During the COVID-19 global pandemic period, cyberbullying grew exponentially as students were essentially working online. We did a scoping study to understand the state of the art referring to academic publications in Portuguese related to cyberbullying in Portugal.  We identified 316 articles in the RCAAP database related to the topic and, after the inclusion and exclusion criteria, 13 articles were deeply analyzed. The conclusions suggest that cyberbullying has more harmful effects than traditional bullying; the authors highlight the need for teacher training to identify signs of cyberbullying; and the importance of intervention projects to inform the community – teachers, students and parents – about how to avoid behaviors that enhance cyberbullying. At the same time, data from a questionnaire survey applied to 96 teachers made it possible to validate the need for training and the importance of having intervention programs that enable the fight against cyberbullying.
Keywords: Cyberbullying; Scoping Study